Randomised controlled study to compare preoperative and postoperative effectiveness of rectal misoprostol for preventing blood loss in elective caesarean delivery - Upadhyay, Priyanka; Wani, Iram; Khan, Ruhina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Comparison between pre-operative and post-operative effectiveness of rectal misoprostol for preventing blood loss in elective caesarean delivery. Methods: A single-blind randomized controlled study of 180 full-term pregnant women were scheduled for elective caesarean delivery. Computerized random allocation of women were done in group 1 to receive 400μg rectal misoprostol at urinary catheter insertion plus 400μg rectally after abdominal closure (preoperative group i.e. group 1, n=90) and group 2 who received 800μg of rectal misoprostol after abdominal closure (postoperative group i.e. group 2, n=90). Primary result was intraoperative blood loss. Results: Intraoperative blood loss was significantly lower in the preoperative misoprostol group who was compared with the postoperative group (526.3±112.8 ml versus 735.4±135.7 ml; p<0.001). Postpartum hemorrhage (PPH) during the first 24 hours after delivery was also lower in the preoperative group against the post-operative group (205.1±77.4 ml versus 289.5±130.1 ml; p<0.001). Fewer women in the preoperative group needed additional uterotonics (8 versus 19; p<0.001) and after delivery, the decrease in haemoglobin levels was also significantly less in the preoperative group (−6.25 versus −14.28%; p<0.001). Conclusions: Preoperative rectal administration of misoprostol significantly reduced intraoperative and postoperative blood loss during and after elective caesarean delivery.